Foreign policy imperatives for the development of the Visegrad Group and Ukraine - Кольцов, Віталій Михайлович; Кольцов, В. М.; Кольцов, Виталий Михайлович; Koltsov, Vitalii M.; Ломжець, Юлія Вікторівна; Ломжець, Ю. В.; Ломжец, Юлия Викторовна; Lomzhets, Yuliia V. (Baltija Publishing, 2020)
The article is devoted to the analysis of the main stages of creation and development of the Visegrad Group as a regional grouping, which is successfully developing when being a member of NATO and the European Union. This kind of research is especially relevant in connection with the exacerbation of the economic crisis due to the COVID-19 pandemic. The purpose of the research is to analyze the strategic stages of creation and development of various cooperative aspects of the Visegrad countries; such a format of interaction has not lost its relevance after accession to the European Union. Analytical separation of periodization of the stages of formation, identification of problems and solutions faced by the Visegrad group’s countries is important for creating a modern economic and political worldview of cooperation and indentifying the main areas of cooperation in Europe. Based on the use of documents, including protocols and declarations as a result of meetings at various levels within the Visegrad Group, the specific stages of its development and interaction with Ukraine in a wide range of components that are the essence of Euro-Atlantic integration are analyzed and identified. Specific examples illustrate that Ukraine has always been in the field of key interests of the Visegrad Four, getting effective assistance and support in various forms from it. There have been identified not only practical issues of regional cooperation and security, but also some aspects of the value and civilization dimension. The member countries of the Visegrad Group, having initiated the format of cooperation “V4 + Ukraine”, took an active part in the most important processes that Ukraine went through on its way. The assumption is proved that the experience of the Visegrad countries is relevant and useful for Ukraine on the way to the realization of its Euro-Atlantic integration aspirations. Despite the difficulties within the European Union, between Ukraine and some of the signatories of the 1991 Visegrad Declaration, cooperation with Poland, the Czech Republic, Slovakia and Hungary is the most effective communication platform for intensifying a broad dialogue between Ukraine and the European Union.

Стаття присвячена аналізу основних етапів створення та розвитку Вишеградської групи як регіонального угруповання, яке успішно розвивається, будучи членом НАТО та Європейського Союзу. Такого роду дослідження особливо актуальні у зв’язку із загостренням економічної кризи через пандемію COVID-19. Метою дослідження є аналіз стратегічних етапів створення та розвитку різних аспектів кооперації країн Вишеградської області; такий формат взаємодії не втратив своєї актуальності і після вступу до Європейського Союзу. Аналітичне виділення періодизації етапів становлення, визначення проблем і шляхів вирішення, з якими стикаються країни Вишеградської групи, є важливим для створення сучасного економічного та політичного світогляду співробітництва та визначення основних напрямків співпраці в Європі. На основі використання документів, у тому числі протоколів та декларацій за результатами зустрічей на різних рівнях у рамках Вишеградської групи, проаналізовано та визначено конкретні етапи її розвитку та взаємодії з Україною за широким спектром компонентів, що є сутністю євроатлантичної інтеграції. Конкретні приклади свідчать про те, що Україна завжди була в полі ключових інтересів Вишеградської четвірки, отримуючи від неї дієву допомогу та підтримку в різних формах. Визначено не лише практичні питання регіонального співробітництва та безпеки, а й окремі аспекти ціннісного та цивілізаційного виміру. Країни-учасниці Вишеградської групи, започаткувавши формат співпраці «V4 + Україна», взяли активну участь у найважливіших процесах, які пройшла Україна на своєму шляху. Обґрунтовано припущення, що досвід Вишеградських країн є актуальним і корисним для України на шляху реалізації її євроатлантичних інтеграційних прагнень. Незважаючи на труднощі всередині Європейського Союзу, між Україною та деякими з підписантів Вишеградської декларації 1991 року співпраця з Польщею, Чехією, Словаччиною та Угорщиною є найефективнішою комунікаційною платформою для активізації широкого діалогу між Україною та Європейським Союзом.
Koltsov V. Foreign policy imperatives for the development of the Visegrad Group and Ukraine / V. Koltsov, Y. Lomzhets // Baltic Journal of Economic Studies. – Vol. 6(4). - Baltija Publishing, 2020. - P. 81-89.
Keywords: Visegrad Group; Visegrad Four (V4); European Union (EU); NATO; Ukraine; integration; Вишеградська група; Вишеградська четвірка (V4); Європейський Союз (ЄС); НАТО; Україна; інтеграція; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law